Antimicrobial Resistance among Salmonella and Shigella Isolates in Five Canadian Provinces (1997 to 2000) - Leah J Martin; James Flint; André Ravel; Lucie Dutil; Kathryn Doré; Marie Louie; Frances Jamieson; Sam Ratnam (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: To describe rates of antimicrobial resistance (AMR) among Salmonella and Shigella isolates reported in five Canadian provinces, focusing on clinically important antimicrobials.